2017
DOI: 10.1371/journal.pone.0186980
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and grazing on soil organic carbon storage in grasslands along the Eurasian steppe eastern transect

Abstract: Soil represents the largest terrestrial organic carbon pool. To address global climate change, it is essential to explore the soil organic carbon storage patterns and their controlling factors. We investigated the soil organic carbon density (SOCD) in 48 grassland sites along the Eurasian steppe eastern transect (ESET) region, which covers the Inner Mongolia grassland subregion and Mongolia grasslands subregion. Specifically, we analyzed the SOCD in the top 30 cm soil layer and its relationships with climatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 62 publications
3
24
0
Order By: Relevance
“…These variations with climatic gradient, although not statistically significant, could imply that climate influences carbon storage. Similar findings were reported previously (Schippers et al 2015;Zhao et al 2017) and demonstrated that carbon storage was strongly correlated with mean annual temperature and mean annual precipitation. In fact, high temperatures in tropical forests induce higher evapotranspiration and water stress, reducing therefore photosynthesis, tree growth, biomass production (Schippers et al 2015) and carbon sequestration.…”
Section: Factors Influencing Biomass Production and Carbon Storagesupporting
confidence: 92%
“…These variations with climatic gradient, although not statistically significant, could imply that climate influences carbon storage. Similar findings were reported previously (Schippers et al 2015;Zhao et al 2017) and demonstrated that carbon storage was strongly correlated with mean annual temperature and mean annual precipitation. In fact, high temperatures in tropical forests induce higher evapotranspiration and water stress, reducing therefore photosynthesis, tree growth, biomass production (Schippers et al 2015) and carbon sequestration.…”
Section: Factors Influencing Biomass Production and Carbon Storagesupporting
confidence: 92%
“…We believe that this increase in TOC content is due to the grass root system [30], the decomposition of residue, and the presence of root exudates. Organic carbon entering the soil in areas of pasture is due mainly to the decomposition of litter on the surface (0-10 cm) and of the underground roots (20-30 cm) [31].…”
Section: Total Organic Carbon (Toc)mentioning
confidence: 99%
“…Despite the need for precise knowledge on the effects of different land uses on ecosystems for climate change mitigation (Lo et al, 2015), studies addressing grazer-type effects on SOC are scarce (i.e. Zhou et al, 2017;Chang et al, 2018). Considering our results, we suggest conducting more experiments which investigate grazer-type effects on SOC under different soil nutrient conditions and within plant communities with contrasting herbage quality parameters.…”
Section: Geophysical Biochemical and Grazing Management Factors Drivmentioning
confidence: 93%
“…It is known that herbivores can affect SOC through different paths, such as regulating the quantity and quality of organic matter returned to soil (Bardgett and Wardle, 2003) or affecting soil respiration and nutrients by animal trampling or soil microbiota alteration (Lu et al, 2017). Several studies confirmed the interaction between grazing and other SOC drivers at diverse scales (Abdalla et al, 2018;Eze et al, 2018;Lu et al, , 2017Zhou et al, 2017). Hence, grazing management may be considered a SOC driver with effects at multiple levels of the driver hierarchy ( Fig.…”
Section: Introductionmentioning
confidence: 99%